Mapping Symbols to Sounds: Electrophysiological Correlates of the Impaired Reading Process in Dyslexia - Widmann, Andreas; Schröger, Erich; Tervaniemi, Mari; Pakarinen, Satu; Kujala, Teija (Frontiers in Psychology, 2012)
Dyslexic and control first grade school children were compared in a Symbol-to-Sound matching test based on a nonlinguistic audiovisual training which is known to have a remediating effect on dyslexia. Visual symbol patterns had to be matched with predicted sound patterns. Sounds incongruent with the corresponding visual symbol (thus not matching the prediction) elicited the N2b and P3a event-related potential (ERP) components relative to congruent sounds in control children. Their ERPs resembled the ERP effects previously reported for healthy adults with this paradigm. In dyslexic children, N2b onset latency was delayed and its amplitude significantly reduced over left hemisphere whereas P3a was absent. Moreover, N2b amplitudes significantly correlated with the reading skills. ERPs to sound changes in a control condition were unaffected. In addition, correctly predicted sounds, that is, sounds that are congruent with the visual symbol, elicited an early induced auditory gamma band response (GBR) reflecting synchronization of brain activity in normal-reading children as previously observed in healthy adults. However, dyslexic children showed no GBR. This indicates that visual symbolic and auditory sensory information are not integrated into a unitary audiovisual object representation in them. Finally, incongruent sounds were followed by a later desynchronization of brain activity in the gamma band in both groups. This desynchronization was significantly larger in dyslexic children. Although both groups accomplished the task successfully remarkable group differences in brain responses suggest that normal-reading children and dyslexic children recruit (partly) different brain mechanisms when solving the task. We propose that abnormal ERPs and GBRs in dyslexic readers indicate a deficit resulting in a widespread impairment in processing and integrating auditory and visual information and contributing to the reading impairment in dyslexia.